The integrated stress response protects against ER stress but is not required for altered translation and lifespan from dietary restriction in Caenorhabditis elegans - Ma, Zhengxin; Horrocks, Jordan; Mir, Dilawar A.; Cox, Matthew; Ruzga, Marissa; Rollins, Jarod; Rogers, Aric N. (Frontiers in Cell and Developmental Biology, 2023)
The highly conserved integrated stress response (ISR) reduces and redirects mRNA translation in response to certain forms of stress and nutrient limitation. It is activated when kinases phosphorylate a key residue in the alpha subunit of eukaryotic translation initiation factor 2 (eIF2). General Control Nonderepressible-2 (GCN2) is activated to phosphorylate eIF2α by the presence of uncharged tRNA associated with nutrient scarcity, while protein kinase R-like ER kinase-1 (PERK) is activated during the ER unfolded protein response (UPR ER ). Here, we investigated the role of the ISR during nutrient limitation and ER stress with respect to changes in protein synthesis, translationally driven mRNA turnover, and survival in C. elegans. We found that, while GCN2 phosphorylates eIF2α when nutrients are restricted, the ability to phosphorylate eIF2α is not required for changes in translation, nonsense-mediated decay, or lifespan associated with dietary restriction (DR). Interestingly, loss of both GCN2 and PERK abolishes increased lifespan associated with DR, indicating the possibility of other substrates for these kinases. The ISR was not dispensable under ER stress conditions, as demonstrated by the requirement for PERK and eIF2α phosphorylation for decreased translation and wild type-like survival. Taken together, results indicate that the ISR is critical for ER stress and that other translation regulatory mechanisms are sufficient for increased lifespan under DR.